Sport-Orthopädie - Kemmler W; Froehlich M; von Stengel S; Kleinöder H (Dynamic Media Sales Verlag, 2016)
Whole-body electromyostimulation (WB-EMS) is a young and time-effective training technology. Comparing the effect of WB-EMS with conventional resistance training,both methods were reported to be similarly effective on muscle mass, strength and cardiometabolic risk. However, due to its exceptional time efficiency, joint friendliness and individualized setting, WB-EMS may be a good choice for people unable or simply unwilling to conduct intense resistance training protocols. However, recent literature has reported negative side-effects concerning WB-EMS-induced rhabdomyolysis. Indeed, due to the ability to innervate large muscle areas simultaneously with dedicated individual intensity per muscle group, WB-EMS features many factors known to be associated with muscle damage. A recent WB-EMS study applying an initial application to exhaustion to healthy novices confirmed the reported exceptionally high creatine-kinase (CK) concentrations. Although the study did not detect any of the reported clinical consequences of this severe rhabdomyolysis (i.e. 50fold increase of resting CK), in less fit subjects who were neither optimally prepared nor supervised, initial WB-EMS to exertion may have more far-reaching consequences. Of importance, a subsequent WB-EMS conditioning phase of 10 weeks completed by a second WB-EMS test application to exhaustion demonstrated CK-peaks in the range of conventional resistance exercise. Thus, in summary (a) too intense initial WB-EMS may indeed result in a severe rhabdomyolysis (b) thus, initial WB-EMS application to exhaustion must be strictly avoided, and (c) frequent WB-EMS application demonstrated a very pronounced repeated bout effect after a short conditioning phase.KEY WORDS: Electrostimulation, Creatine-Kinase, Rhabdomyolysis, Recommendation WB-EMS